2004
DOI: 10.1002/mds.20119
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral chorea–ballism associated with hyperthyroidism

Abstract: We describe a 50-year-old patient with four episodes of recurrent bilateral chorea-ballism (BCB) and associated hyperthyroidism. Reappearance of BCB, associated with increased serum levels of thyroid hormones and lack of relevant changes on brain computed tomography/magnetic resonance imaging scans, suggested that the involuntary movements were likely due to thyrotoxicosis-induced biochemical changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 14 publications
2
23
1
1
Order By: Relevance
“…In an early report, basal ganglia anatomy was unremarkable at autopsy [6]. This is in line with normal brain imaging in our patient and others [2,4]. The association of chorea with streptococcal infections, systemic lupus erythematosus and antiphospholipid antibody syndrome has led some authors to suggest an autoimmune mechanism for thyrotoxic chorea [7].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In an early report, basal ganglia anatomy was unremarkable at autopsy [6]. This is in line with normal brain imaging in our patient and others [2,4]. The association of chorea with streptococcal infections, systemic lupus erythematosus and antiphospholipid antibody syndrome has led some authors to suggest an autoimmune mechanism for thyrotoxic chorea [7].…”
Section: Discussionsupporting
confidence: 91%
“…Thyrotoxic involuntary movements besides tremor may manifest as classical choreathetosis (as in our patient), paroxysmal chorea [3], paroxysmal kinesigenic chorea [1], bilateral chorea-ballism [4] and hemichorea [5]. The underlying mechanisms of thyrotoxic chorea remain unknown.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…3 Although most cases involve Grave's disease, a few reports of chorea due to iatrogenic thyrotoxicosis have been published. 7 The pathophysiology of hyperthyroidism-related chorea is poorly understood, which is not surprising in view of the wide range of metabolic pathways affected by thyroid hormones.…”
mentioning
confidence: 99%
“…It has been suggested that thyroid hormones could functionally affect the dopaminergic system within the basal ganglia, possibly through an increased sensitivity of the dopaminergic receptors. 3 However, thyroid hormones also play an important role in regulating central noradrenergic, serotoninergic, and cholinergic systems, and complex interactions may occur. 8,9 Furthermore, thyroid hormones also control gene expression in the nervous central system.…”
mentioning
confidence: 99%